(untitled) (Andamios, Revista de Investigación Social, 2025)
This research’s purpose is to describe and analyze, with an anthropological approach, data constructed through interviews, participant observation, and autoethnography, the organization and sustainability of a Learning Community in ​​Guadalajara´s Metropolitan Area. First, I explain what Learning Communities are, the types they offer, and why they have begun to proliferate in Mexico. I then turn to a case study analysis to explain their organization, functioning, and the problems they face in their daily lives, emphasizing the experiences and strategies that give value to “being in community” despite the capitalist and individualist dynamics prevailing in urban contexts. This, as discussed in the conclusions, sheds light on contemporary organizational processes.